Problems and prospects of the development of taxation of cryptocurrencies transactions - O.V.; O.S.; O.V. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article is devoted to the problems of taxation of transactions with cryptocurrencies. Disagreements in the interpretation of the essence of cryptocurrencies in the recommendations of the regulators were revealed, which leads to the lack of a reasonable approach to the reflection of such transactions in accounting and the subsequent determination of the tax base. The current legislation and explanations of tax authorities regarding the declaration and taxation of transactions with cryptocurrencies were analyzed and the absence of special rules regarding the taxation of such transactions was found. The general principles of taxation of operations with cryptocurrencies are characterized by a significant tax burden on such operations, which, in conditions of anonymity of cryptowallet owners, leads to concealment of such operations and avoidance of their taxation. The draft laws on regulation of circulation and taxation of transactions with cryptocurrencies were analyzed, the advantages of which compared to the current legislation are a reduction in the rates of taxation of such transactions by personal income tax and income tax; VAT exemption. In order to ensure the possibility of state control of transactions with cryptocurrencies in matters of taxation and financial monitoring, it is proposed to include cryptocurrency exchanges in the list of subjects of primary financial monitoring.